(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, the current issues of speech therapy, which is considered the main department of special pedagogy, about speech and its deficiencies, elimination of defects in the formation and development of children’s speech, speech therapy games, the use of speech therapy games to eliminate speech disorders, and their main aspects explained